Pembelajaran Biologi Terintegrasi Pendidikan Pelestarian Lingkungan Di Madrasah Berbasis Pesantren : Studi Pada Madrasah Aliyah Pondok Pesantren Darul Amal Kota Metro Lampung - munawaroh, imroatul (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
This study examines the integration of biology learning with environmental conservation education in Islamic boarding school-based Islamic Senior High Schools (Madrasah Aliyah) as a response to the low affective and psychomotor involvement of students in biology learning, which has tended to be theoretical and fragmented. The purpose of this study was to explore the integrative practices implemented in Islamic boarding school-based Islamic Senior High Schools (Madrasah Aliyah) and to assess their effectiveness in shaping students' ecological awareness. This study used a descriptive qualitative approach with a case study design, through observation, in-depth interviews, and documentation techniques. The results showed that the madrasah had implemented the Natural Exploration Method (MJAS) which makes the surrounding environment a learning laboratory. Students were actively involved in activities such as tree planting, waste sorting, and the use of biogas reactors as a medium for learning bioremediation. These findings indicate that the integration of biology learning and environmental conservation simultaneously builds contextual knowledge, scientific skills, and ecological awareness in students. Based on this study, it is concluded that this practice reflects the ecopedagogy approach and the principles of sustainable education (Education for Sustainable Development), and strengthens the position of madrasas as transformative educational agents capable of producing generations with ecological insight within the framework of Islamic values.